Current peptide and protein candidates challenging HIV therapy beyond the vaccine Era - Koollawat Chupradit (2018)
© 2017 by the authors.Licensee MDPI, Basel, Switzerland. Human immunodeficiency virus (HIV) is a causative agent of acquired immune deficiency syndrome (AIDS). Highly active antiretroviral therapy (HAART) can slow down the replication of HIV-1, leading to an improvement in the survival of HIV-1-infected patients. However, drug toxicities and poor drug administration has led to the emergence of a drug-resistant strain. HIV-1 immunotherapy has been continuously developed, but antibody therapy and HIV vaccines take time to improve its efficiency and have limitations. HIV-1-specific chimeric antigen receptor (CAR)- based immunotherapy founded on neutralizing antibodies is now being developed. In HIV-1 therapy, anti-HIV chimeric antigen receptors showed promising data in the suppression of HIV-1 replication; however, autologous transfusion is still a problem. This has led to the development of effective peptides and proteins for an alternative HIV-1 treatment. In this paper, we provide a comprehensive review of potent anti-HIV-1 peptides and proteins that reveal promising therapeutic activities. The inhibitory mechanisms of each therapeutic molecule in the different stages of the HIV- 1 life cycle will be discussed herein.